Prenatal diagnosis of microcephaly as shown by plateauing of head circumference growth during the 3rd trimester in a fetus with a CCND2 inverse growth variant. (28th April 2022) - Malinger, Gustavo; Haratz Krajden, Karina; Brinbaum, Roee; Tsur, Erez; Berger, Racheli; Shohat, Mordechai
Key points: What's already known? Variants in CCND2 gene are known to cause syndromic macrocephaly. Recently inverse growth proximal variants were described in five individuals with microcephaly. What does this study add? CCND2 loss of function distal variants can cause fetal microcephaly.